Formulation And In Vitro Evaluation Of Sustained-Release Canagliflozin Nano-Particles For The Treatment Of Diabetic - Ali Khan, Sultan Moaaz; Kumar, Sachin (Journal of Neonatal Surgery, 2025)
The development of sustained-release Canagliflozin (CFZ) nanoparticles marks a significant advancement in the management of type 2 diabetes mellitus, particularly for patients requiring long-term glycemic control. This study meticulously evaluated the physicochemical properties, in vitro drug release profiles, and stability of CFZ-loaded nanoparticles, aiming to enhance therapeutic efficacy and patient compliance. In summary, the development of CFZ nanoparticles, along with the utilization of polymeric nanoparticles and stimuli-responsive systems, represents a promising strategy to enhance the oral bioavailability and therapeutic efficacy of this poorly soluble drug. These advancements in drug delivery technologies hold significant potential for improving the treatment of conditions such as diabetes.